Possible Allergenic Role of Tropomyosin in Patients with Adverse Reactions after Fish Intake. (19th May 2018) - González-Fernández, Juan; Alguacil-Guillén, Marina; Cuéllar, Carmen; Daschner, Alvaro
ABSTRACT: In a recent case report, patient's anti-fish tropomyosin IgE was associated with gastrointestinal symptoms. We aimed to demonstrate on a wider scale that the panallergen tropomyosin should not be limited to invertebrate species and that clinically relevant reactions could be elicited by vertebrate tropomyosin. On the whole, 19 patients with adverse reactions after fish intake and showing negative skin tests with commercial fish extracts were included. Fish tropomyosin was recognized by 10/19 patients' IgE by immunoblotting. All patients with gastrointestinal complaints after fish intake (6/6) showed an IgE band matching with tropomyosin. Cod, albacore, and swordfish tropomyosins were recognized by most patients although 3/10 patients did not claim adverse reactions to these fish species. Immunoblotting with a battery of antigens from different fish species have a high yield of positivity at a band matching with tropomyosin molecular weight, even if they have not been claimed to be causative agents of symptoms. Tropomyosin is therefore a good candidate to be investigated as a clinically relevant fish allergen in patients who report adverse reactions after fish intake.